An Action Semantics for ML Concurrency Primitives - Mosses, Peter D.; Musicante, Martín (BRICS Report Series, 1994)
This paper is about the recently-developed framework of action semantics. The pragmatic qualities of action semantic descriptions are particularly good, which encourages their use in industrial-scale applications where semantic descriptions are needed, e.g., compiler development. The paper has two main aims: to demonstrate the remarkable extensibility of action semantic descriptions, and to illustrate the action semantics treatment of concurrency. These aims are achieved simultaneously, by first giving the description of a sequential (ML-like) programming language fragment, and then extending the described language with some concurrency primitives (taken from CML). The action semantic description of the sequential part of the language does not change at all when the concurrency primitives are added, it merely gets augmented by the description of the new features!